2016
DOI: 10.1002/2015jc011186
|View full text |Cite
|
Sign up to set email alerts
|

The impact of variable sea ice roughness on changes in Arctic Ocean surface stress: A model study

Abstract: The Arctic sea ice cover is thinning and retreating, causing changes in surface roughness that in turn modify the momentum flux from the atmosphere through the ice into the ocean. New model simulations comprising variable sea ice drag coefficients for both the air and water interface demonstrate that the heterogeneity in sea ice surface roughness significantly impacts the spatial distribution and trends of ocean surface stress during the last decades. Simulations with constant sea ice drag coefficients as used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
4

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 44 publications
(96 reference statements)
6
93
4
Order By: Relevance
“…Martin et al (2014) found that, in the 2000s, the summertime ice pack was experiencing longer periods of "optimal ice concentration" (80-90 % ice concentration) for momentum transfer to the ocean. However, in this study, and a follow-up study including variable form drag (Martin et al, 2016), they reported a negative trend in summertime ocean surface stress; despite increased ice-ocean stress, the loss of summer sea ice coverage led to an overall decrease in the ocean surface stress because the atmosphere-ocean stress is smaller than ice-ocean stress. Wintertime circulation changes are likely a result of reduced ice strength and reduced ice interaction forces.…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…Martin et al (2014) found that, in the 2000s, the summertime ice pack was experiencing longer periods of "optimal ice concentration" (80-90 % ice concentration) for momentum transfer to the ocean. However, in this study, and a follow-up study including variable form drag (Martin et al, 2016), they reported a negative trend in summertime ocean surface stress; despite increased ice-ocean stress, the loss of summer sea ice coverage led to an overall decrease in the ocean surface stress because the atmosphere-ocean stress is smaller than ice-ocean stress. Wintertime circulation changes are likely a result of reduced ice strength and reduced ice interaction forces.…”
Section: Discussioncontrasting
confidence: 48%
“…However, Martin et al (2016) found reduced wintertime ocean surface stress due to ice smoothing and decreased form drag associated with loss of deformed thick ice. So, whilst observations make it clear that ocean surface stress increased in the Arctic Ocean, particularly in the late 2000s, contradictory model results show that more work is needed to refine the representation of atmosphere-ice-ocean coupling in models before we can fully attribute causality to these increases (Martin et al, 2016). An aspect of ice-ocean coupling that has been lacking is long-term observations of time-variable upper-ocean circulation, which this study has helped to provide.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations